Bilateral BrightOcular iris implants necessitating explantation and subsequent endothelial keratoplasty - Zale Mednick; Devin Betsch; Tanguy Boutin; Adi Einan-Lifshitz; Nir Sorkin; Allan Slomovic (American Journal of Ophthalmology Case Reports, 2018)
Purpose: To demonstrate the dangers associated with the BrightOcular iris implant, a model that had initially been touted as safer than its predecessors. Observations: A 41-year-old male presented with decreased vision in both eyes, approximately two years following bilateral BrightOcular cosmetic iris implantation performed in Mexico. On initial consultation, he was found to have bilateral corneal decompensation with stromal edema and a significantly reduced endothelial cell count (ECC). On follow up 5 weeks later, his vision and corneal edema had further detriorated. In the following month, he underwent explantation of the cosmetic iris implants in both eyes. Significant corneal edema persisted in the right eye several months post-operatively, to the point of necessitating endothelial keratoplasty. Conclusions and importance: Despite numerous reports in the literature of the significant ocular complications that can arise secondary to cosmetic iris implantation, individuals continue to willingly undergo this surgery. Our intention with presenting this case to the ophthalmologic community is two-fold: to highlight the ongoing clinical risk that BrightOcular devices pose, despite being marketed as safer than the older NewColourIris models, and to stress the urgency with which cosmetic iris implants should be removed from the eye. Keywords: Cosmetic iris implants, BrightOcular, Iris implant removal, Corneal decompensation, Endothelial keratoplasty